HbA1c is inversely associated with thyroid cysts in a euthyroid population: A cross-sectional study. - Yuji Shimizu (Public Library of Science (PLoS), 2021)
Anti-thyroid peroxidase antibody (TPO-Ab) is revealed to be inversely associated with thyroid cysts among euthyroid population. TPO-Ab causes autoimmune thyroiditis by bolstering thyroid inflammation. Therefore, at least partly, absence of thyroid cysts could indicate latent thyroid damage. Since participants with subclinical hypothyroidism are reported to have higher HbA1c than normal healthy controls, HbA1c could be inversely associated with thyroid cysts through a mechanism reflecting latent thyroid damage. To investigate the association between HbA1c and thyroid cysts among a euthyroid population, a cross-sectional study was conducted on 1,724 Japanese individuals who were within the normal range of thyroid function [i.e., normal range of free triiodothyronine (T3) and free thyroxine (T4)] and aged 40-74 years. Among this study population, 564 were diagnosed with thyroid cysts. Independently of thyroid related hormones [thyroid stimulating hormone (TSH), free T3, and free T4] and known cardiovascular risk factors, HbA1c was found to be significantly inversely associated with the presence of thyroid cysts. This association remained significant even after this analysis was limited to participants within a normal range of TSH. The fully adjusted odds ratios (ORs) of thyroid cysts for 1 standard deviation (SD) increment of HbA1c were 0.84 (0.74, 0.95) for total participants and 0.80 (0.70, 0.92) for participants within a normal range of TSH. Among participants with normal thyroid function, HbA1c was inversely associated with the presence of thyroid cysts. The absence of thyroid cysts and higher levels of HbA1c could indicate the latent functional damage of the thyroid.